Factors influencing fans’ spectating experience and configuration effects in CBA league - Duan Yu; Hongwei Fan; Ning Zhang (PLoS ONE, 2025)
The low satisfaction of fans’ spectator experience, the weak willingness to continue to watch games have become the realistic barriers limiting the sustained and favorable development of Chinese Basketball Association league (CBA League). Using Structural Equation Modeling (SEM) and Fuzzy-set Qualitative Comparative Analysis (fsQCA), this study clarifies the complex causal relationship behind the phenomenon of fans’ spectator experience, explore the linkage mechanism between different influencing factors of spectator experience. Also constructs a variety of grouping paths to enhance the fans’ spectator experience in the CBA League. The results shows that Sense, Feel, Think, Act, Relate and Spectator Service all positively affect the satisfaction of the live Spectator experience in the CBA League. Among six influencing factors, none of them is the necessary condition for high satisfaction of Fans’ Spectator Experience. In this way, the characteristics of multi-factors and different paths of the live Spectator experience were verified. Influential factors were coupled to form six grouping paths for high satisfaction of the fans’ spectator experience, which were categorized into two types of configurations by combining the grouping characteristics: 1) Led by spectator service, feel and act experience co-driven, 2) Spectator service and think experience co-driven. The findings provide theoretical guidance for enhancing fan experience and meeting the practical needs of cultivating loyal CBA fan groups while expanding the league’s influence.